Human mobility networks reveal increased segregation in large cities - Nilforoshan, Hamed; Looi, Wenli; Pierson, Emma; Villanueva, Blanca; Fishman, Nic; Chen, Yiling; Sholar, John; Redbird, Beth; Grusky, David; Leskovec, Jure (Nature (London), 2023)
A long-standing expectation is that large, dense and cosmopolitan areas support socioeconomic mixing and exposure among diverse individuals 1 – 6 . Assessing this hypothesis has been difficult because previous measures of socioeconomic mixing have relied on static residential housing data rather than real-life exposures among people at work, in places of leisure and in home neighbourhoods 7 , 8 . Here we develop a measure of exposure segregation that captures the socioeconomic diversity of these everyday encounters. Using mobile phone mobility data to represent 1.6 billion real-world exposures among 9.6 million people in the United States, we measure exposure segregation across 382 metropolitan statistical areas (MSAs) and 2,829 counties. We find that exposure segregation is 67% higher in the ten largest MSAs than in small MSAs with fewer than 100,000 residents. This means that, contrary to expectations, residents of large cosmopolitan areas have less exposure to a socioeconomically diverse range of individuals. Second, we find that the increased socioeconomic segregation in large cities arises because they offer a greater choice of differentiated spaces targeted to specific socioeconomic groups. Third, we find that this segregation-increasing effect is countered when a city’s hubs (such as shopping centres) are positioned to bridge diverse neighbourhoods and therefore attract people of all socioeconomic statuses. Our findings challenge a long-standing conjecture in human geography and highlight how urban design can both prevent and facilitate encounters among diverse individuals. There is extreme socioeconomic segregation in large US cities, arising from a greater choice of differentiated spaces targeted to specific socioeconomic groups, which can be countered by positioning city hubs (such as shopping centres) to bridge diverse neighbourhoods.